The Effect of Job Quality And Competence on The Performance of The Quality Control Department Through Supervision : (A Study at the Construction Manufacturing Company PT. XYZ) - Juniar Rizqi, Rizal; Vip Paramarta; Farida Yuliaty (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyse the effect of work quality and competence on the performance of the Quality Control department in construction manufacturing companies, with supervision as an intervening variable. The background of this study stems from the important role of Quality Control in maintaining product quality, where factors such as work quality, employee competence, and the effectiveness of supervision are believed to contribute directly or indirectly to performance. The research method used a quantitative approach with path analysis techniques. Data were obtained through the distribution of questionnaires to employees working in the Quality Control department. The variables measured included job quality (X1), competence (X2), supervision (Y), and performance (Z). The results of the study indicate that work quality and competence have a positive and significant effect on supervision. In addition, both work quality and competence have a direct effect on employee performance. Supervision has the most dominant effect on performance, while also acting as a mediating variable that strengthens the effect of work quality and competence on performance. Thus, improving work quality and employee competence will have a more optimal effect on performance if supported by effective supervision. The implications of this study emphasise the importance of companies developing the technical and professional skills of Quality Control employees, strengthening their monitoring systems, and integrating both to achieve sustainable optimal performance.